The New Entity of Paranodopathies: A Target Structure with Therapeutic Consequences - Doppler, Kathrin; Sommer, Claudia (Neurology International Open, 2017)
Autoimmune neuropathies with autoantibodies against paranodal proteins have been described in the last few years. They comprise a subgroup of inflammatory neuropathies with IgG4 autoantibodies against the paranodal proteins neurofascin-155, contactin-1 and caspr-1. Although this subtype of autoimmune neuropathy represents less than 10% of all patients diagnosed with CIDP, it is of high interest as they show a different response to treatment. Even though there are no therapeutic studies available due to the limited number of patients identified so far, all case reports published so far report an excellent response to treatment with rituximab, and in most cases no response to treatment with IVIG, the standard therapy of CIDP. The typical clinical picture of patients with autoantibodies against paranodal proteins is characterized by an acute onset of a severe predominantly motor neuropathy, often accompanied by action tremor and sensory ataxia, with demyelinating features in the nerve conduction studies but an axonal histological phenotype. The latter may be explained by the pathogenetic concept of a paranodopathy/nodopathy, a disease of the paranode/node of Ranvier.
Keywords: neuropathy; node of Ranvier; autoantibody; CIDP